A survey of intelligent energy management based on learning heuristic - Musa Abdullah Hamed; Esam Taha Yassin Hussein; Wesam Mohammed Jasim Abd (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Human activities are dependent on energy and lifestyles that important provide services on a daily basis. Currently, polluting and energy consumption worldwide is dominated by sources non-renewable, for instance fossil fuels. Due to their environmental impact, research and investment have increased in alternative and renewable energy sources, such as photovoltaic and wind energy. Buildings use energy management systems to monitor real-time consumption and plan the operation of appliances so that the energy bill is minimized or based on other factors. The purpose of energy management systems in buildings is mainly to monitor real-time energy consumption and adjust the device's operation to minimize energy bills or achieve another specific goal. The purpose of this work is review the latest literature on energy management systems based on heuristic learning of buildings in the smart home. In addition, the literature has been updated a list of techniques that managed appliances and the planning goals and how use these techniques to in the energy scheduling.